Influence of Welding Process on Mechanical and Corrosion Behavior of AA2519 Aluminium Alloy - G. Siva Prasad; K. Srinivasa Rao; G. Madhusudhan Reddy (Technological Innovation in Engineering Research Vol. 7, 2022)
AA2519 alloy is emerged as upgrade version of AA2219 Al- alloy with an aim to improve the ballistic resistance and strength to weight ratio. In general, formation of oxide layers, solidification cracking, and porosity are the significant problems raised during welding. Given the above, the present work is planned to investigate the effect of welding process on microstructural changes, corrosion behavior and mechanical properties. Gas Tungsten Arc Welding (GTAW) and Friction Stir Welding (FSW) were used in the present work to weld 10mm thick plates of AA2519 Al-alloys. In order to investigate the pitting corrosion behaviour, potentiodynamic polarization tests were carried out in the aqueous solution of 3.5 percent NaCl in an aerated atmosphere. Exfoliation corrosion investigations using the EXCO solution are performed for various time lapses. According to the research, AA2519 FS welds exhibit superior mechanical and corrosion resistance than GTA welds. Undissolved strengthening precipitates like Al2CuMg, Al3Zr, and Al3Ti were discovered to provide the mechanism for a better combination of hardness and corrosion resistance. Insulation paths of galvanic cell formation between Al2Cu and \(α\) -Al matrix are given by these strengthening precipitates.